Cylindrical flow regulators with core hole – chamber diameter effect - Ochowiak, Marek; Włodarczak, Sylwia; Pavlenko, Ivan; Krupińska, Anżelika; Markowska, Małgorzata; Dudek, Leszek; Piecka, Cezary (Instal, 2020)
The standard and modified liquid flow regulators were tested in this work. In modified regulators a cylindrical core hole was installed in the regulator axis. It takes the shape of a cylinder, without a base being tangent to the wall of the regulator. It is placed on the wall opposite to the outlet. The „core-hole” effect in the outflow of water from the tank contributes to the stabilization of the outflow, however, for the tested devices, a slight increase in the discharge coefficient was observed, which is undesirable in this case. It should be noted that this increase is small and should not be assessed unequivocally negatively, because stabilization of the core and even outflow of liquid are also important. It has been shown that the value of the discharge coefficient decreases with increasing diameter of the swirl chamber. The research with the participation of cylindrical vortex regulators containing a core hole, which is the subject of this article, is to be an extension of the existing knowledge on this phenomenon.